2016
DOI: 10.5603/kp.a2016.0019
|View full text |Cite
|
Sign up to set email alerts
|

Day by day telemetric care of patients treated with cardiac resynchronisation therapy: first Polish experience

Abstract: A b s t r a c tBackground: Due to the recent rapid increase in the number of patients implanted with pacemakers, cardioverter-defibrillators (ICD), and cardiac resynchronisation therapy devices (CRT), conventional monitoring at specialist clinics is becoming increasingly difficult. The development of technology has enabled remote device monitoring with the use of teletransmission systems. Aim:To assess the effectiveness of transmission and the possibility of using telemetric data for further clinical managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Thus, telemonitoring allows assessing the relevant technical parameters of the device (battery status, electrode function, and system compatibility) and provides other key clinical information (stimulation percentage, arrhythmic episodes, or current intracardiac electrogram) [23,26]. In addition, novel telemetric strategies may provide data on the current clinical status or device alarms, including device-related malfunctions, arrhythmias, heart and respiratory rate statistics, heart sounds, and intrathoracic impedance [28][29][30][31].…”
Section: Remote Monitoring In Patients With Ciedsmentioning
confidence: 99%
“…Thus, telemonitoring allows assessing the relevant technical parameters of the device (battery status, electrode function, and system compatibility) and provides other key clinical information (stimulation percentage, arrhythmic episodes, or current intracardiac electrogram) [23,26]. In addition, novel telemetric strategies may provide data on the current clinical status or device alarms, including device-related malfunctions, arrhythmias, heart and respiratory rate statistics, heart sounds, and intrathoracic impedance [28][29][30][31].…”
Section: Remote Monitoring In Patients With Ciedsmentioning
confidence: 99%
“…8,62 The daily telemetric care of a large population of such CIED patients may be considered triage of high-risk patients, with ongoing selection of individuals who require urgent medical intervention. 64 According to expert consensus, remote monitoring should be available for all patients with CIEDs as part of the standard follow-up strategy, but in particular for patients with HF and cardiac arrhythmias. 8,62 There is urgent need for integrated medical care for patients with HF.…”
Section: Remote Monitoring Of Patients With Cardiac Electronic Implanmentioning
confidence: 99%
“…Importantly, the effectiveness of the therapy may be assessed on an ongoing basis. 64 A survey from the Health Economics Committee of the EHRA 25 showed that early recognition of AF among PM patients, lead failure in ICD patients, and HF worsening in CRT patients were considered essential advantages of remote monitoring. The opportunity comes from dual-chamber devices that can also monitor atrial rhythm, allowing the possibility of recognizing arrhythmias and AF.…”
Section: Remote Monitoring Of Patients With Cardiac Electronic Implanmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are transferred from patient's device into large databases, to which clinicians have internet-based access. The vast majority of relevant technical parameters can be assessed by telemonitoring including recorded arrhythmias, battery longevity, electrodes properties, stimulation percentage, and intra-cardiac electrograms [1,2] When conducted on a daily basis, remote monitoring (RM) of CIEDs is a valuable tool to screen and triage patients at very high risk of deterioration, to which offer personalized medical interventions [3]. Even though remote monitoring of any kind of CIEDs, including permanent pacemakers (PPM), implantable cardioverter defibrillators (ICD) and implantable cardiac monitors (ICM), could offer some advantages to patients and physicians [4], it is especially true for subgroups of patients.…”
Section: Introductionmentioning
confidence: 99%